2012
DOI: 10.1016/j.jacc.2012.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Regional Treatment Effects in Studies of Cardiorenal Drugs

Abstract: Studies are listed in order from top to bottom by percent of U.S. enrollment (shown in the column on right). Circles indicate the point estimate of the difference between log-hazard ratios (U.S. compared with non-U.S.), and arrows represent the 95% confidence interval for this difference.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Empirical evidence indicated the existence of country specific effects of medical interventions. For example, studies conducted in the United States (US) on average reported smaller treatment effects of cardiorenal drugs compared with studies in the non-US countries 103 . A meta-epidemiological study found that RCTs conducted in less developed countries tended to report more favourable results than trials in more developed countries 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Empirical evidence indicated the existence of country specific effects of medical interventions. For example, studies conducted in the United States (US) on average reported smaller treatment effects of cardiorenal drugs compared with studies in the non-US countries 103 . A meta-epidemiological study found that RCTs conducted in less developed countries tended to report more favourable results than trials in more developed countries 12 .…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of 24 cardiovascular and renal drug trials submitted to the FDA in the past 15 years was conducted 45 . In these trials, the percentage of US patients ranged from 3 to 90.…”
Section: Clinical and Statistical Experience Reviewing Clinical Trialsmentioning
confidence: 99%
“…Generalizability or external validity of findings from RCTs is often context dependent, and questionable across different settings or countries [ 56 , 57 ]. For example, studies in the United States on average reported smaller effects of cardiorenal drugs compared with those conducted in other countries [ 58 ]. A study found that RCTs from less developed countries tended to report more favorable results than those from developed countries [ 53 ].…”
Section: Discussionmentioning
confidence: 99%